(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The mechanism of developing arterial hypertension and insulin resistance in individuals with excess body weight is of great importance when determining the treatment strategy, including the selection of medications, dosage, and duration of use, as well as the combination of antihypertensive agents, statins, biguanides, insulin medications, and hepatoprotective and cardioprotective agents. In this regard, antihypertensive drugs, such as losartan and nebivolol, used to treat patients with excess body weight and/or insulin resistance, must meet several criteria: effectively reduce blood pressure throughout the da, have no adverse effects on carbohydrate, lipid, and purine metabolism, possess organoprotective effects, and reduce the risk of developing metabolic syndrome (MS).